Śukla Yajurveda, Vājasaneyi Mādhyandina saṃhitā : sānvaya Marāṭhī bhāshāntarāsaha - Bāpaṭa, Dhuṇḍirāja Gaṇeśa Dīkshita, 1882-1956 (SAMP early 20th-century Indian books project, 1940)
Marathi translation with explanation of Vājasaneyisaṃhitā (Mādhyandinasaṃhitā) from Yajurveda; includes original Sanskrit text.